1977
DOI: 10.1073/pnas.74.8.3119
|View full text |Cite
|
Sign up to set email alerts
|

Primary photochemical event in vision: proton translocation.

Abstract: Picosecond studies of rhodopsin in low-temperature glasses have been carried out in order to observe directly the risetime of prelumirhodopsin, the first intermediate in the visual pathway. Only at 20 K or below can the risetime of this intermediate be resolved and even at 4 K it is astoundingly rapid, about 36 psec. An examination of the Arrhenius dependence on temperature of the rate of formation of prelumirhodopsin shows a strong deviation from linearity at low temperatures, i.e., non-Arrhenius behavior. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
96
1
2

Year Published

1978
1978
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(106 citation statements)
references
References 22 publications
7
96
1
2
Order By: Relevance
“…RESULTS Rhodopsin samples were purified to remove free unbound retinal that might interfere with visual pigment absorption and were solubilized for high optical clarity to minimize light scattering. The rate of production of bathorhodopsin (2,7,8), the low temperature spectra (1,(8)(9)(10)(11), and the quantum yield of bleaching (12)(13)(14) are the same whether rhodopsin is solutTo whom reprint requests should be addressed. …”
mentioning
confidence: 99%
“…RESULTS Rhodopsin samples were purified to remove free unbound retinal that might interfere with visual pigment absorption and were solubilized for high optical clarity to minimize light scattering. The rate of production of bathorhodopsin (2,7,8), the low temperature spectra (1,(8)(9)(10)(11), and the quantum yield of bleaching (12)(13)(14) are the same whether rhodopsin is solutTo whom reprint requests should be addressed. …”
mentioning
confidence: 99%
“…Elucidation of ultrafast dynamics in various systems accelerates development in various applications like photosensors [3][4][5], ultrafast optical switches [6][7][8], and ultrafast optical memories [9][10][11]. Many interesting ultrafast dynamics in biological systems including photosynthesis [12][13][14] and vision processes [15][16][17], were studied by ultrafast spectroscopy using the visible or UV pulse lasers. In these experiments, sometimes the intensities of the generated pulses are not stable due to the various nonlinearities in the generation process.…”
Section: Light Sources For Studying Ultrafast Processesmentioning
confidence: 99%
“…By excitation of cattle rhodopsin at very low temperature (4-35 K), Peters et al (1977) observed the formation of a bathochromic photoproduct which was first assigned as a lowest excited state of rhodopsin and later as a ground state intermediate, named "Batho"' or "prebathorhodopsin" (Honig et al, 1979;Peters and Leonitis, 1982;Ottolenghi, 1982). It decayed to the next bathochromic intermediate (presumably bathorhodopsin) with a time constant of 36 ps at 4 K. Kobayashi (1980) also observed the bathochromic photoproduct [first assigned as an excited state and later as a ground state intermediate named "primerhodopsin" (Ohtani et al, 1988)] by excitation of cattle rhodopsin at room temperature.…”
Section: Primary Intermediate Of Rhodopsinmentioning
confidence: 99%